The Sierra Norte-Ambargasta batholith: Late Ediacaran–Early Cambrian magmatism associated with Pampean transpressional tectonics - Iannizzotto, Noelia (2013)
The Sierra Norte-Ambargasta batholith is one of the largest plutonic expressions of the Pampean orogeny in western Argentina. A thorough petrographic, geochemical, isotopic (Sr and Nd) and geochronological (UePb SHRIMP) study is reported. The batholith comprises granitoid rocks that may be subdivided into those affected by Pampean D2 dextral shearing and mylonization and those emplaced after deformation had ceased; representative samples gave UePb zircon ages of 537 ±4 Ma and 530 ±4 Ma respectively. The earlier, dominant, groupwere derived largely frommetaluminous calc-alkaline subduction-related magmas, whereas the late granites are peraluminous. However, all have relatively high initial 87Sr/86Sr ratios (0.706 to at least 0.710, strongly negative eNdt values (-1.7 to -5.9) and, in some cases inherited 600 Ma and 970 Ma zircon, similar to the isotopic and zircon provenance seen in the metamorphic host rocks. A high degree of contamination of the magmas, possibly anatexis in the case of the post-mylonite granite, is related to emplacement during the latestage transpressional docking of the Pampean terrane against the Rio de la Plata craton. The absence of detrital zircon derived from the craton in either the Pampean metasedimentary host rocks or the batholith supports this collisional model for the Pampean orogen.